Analisis Nilai Edukasi Teater pada Naskah Mamanda di Sanggar Pusaka Saijaan Kotabaru - Normasunah Normasunah; Siti Haryawati (STKIP Paris Barantai, 2020)
This study aims to (1) describe the value of social education in Mamanda traditional theater; (2) to describe the value of cultural education in Mamanda traditional theater. The data obtained came from the observation of the mamanda manuscript at the Saijaan Kotabaru Heritage Center. This type of research is field research and uses descriptive qualitative research methods by observing or observing some mamanda performances and noting some aspects of mamanda stories at the Saijaan Arts Center, Kotabaru Regency. Furthermore, the data obtained is a document for analysis material. The results showed that (1) in the mamanda manuscript at Sanggar Pusaka Saijaan Kotabaru there is a social education value which is an attitude in interaction, which a person uses to interact between individuals, individuals with groups, or groups with the community; (2) in the mamanda manuscript at Sanggar Pusaka Saijaan Kotabaru, there is a cultural education value which is considered good and valuable by a community group or ethnic group which is not necessarily considered good by other people or ethnic groups. Because cultural values ​​limit and give characteristics to a society and its culture. Key words: education value and mamanda